Armageddon - Torrey, Charles C. (Harvard theological review, 1938)
The term “Armageddon,” familiar in English literature, primarily designates the scene of the last great battle at the end of the present age, in which the powers of evil, represented by hostile nations warring against the Kingdom of God, are to be overthrown and destroyed. The name is derived from a passage in the Book of Revelation, 16:16, in which a standing feature of Hebrew eschatology is given a setting characteristic of the apocalypse.